Analisis Pengaruh Pandemi Covid-19 terhadap Tingkat Pendapatan UMKM (Studi Kasus UMKM Lombok Timur) - Yuliana Astuti; Herlina Pusparini; Yusli Mariadi (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
The emergence of covid-19 at the end of 2019 in Wuhan China, is not only a common disaster but a cause of death for those contaminated by the virus known as Covid-19. The virus is not only the pledge but impacted the economic and financial conditions worldwide. The pandemic spread out all over the globe including Indonesia. The main purpose of this research is to analyze the impact of Covid-19 on the financial condition, especially on the Small and Medium Enterprises (UMKM). the where all data has been gathered by The Result of the research indicates that the pandemic so-called Covid-19 is extremely impacted actors of Small and Medium Enterprises (UMKM), they face a statistically significant decrease in income with minus 50% and more every month.